2013
DOI: 10.1093/ejcts/ezt375
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity training and cardiopulmonary exercise testing in patients with chronic obstructive pulmonary disease and non-small-cell lung cancer undergoing lobectomy

Abstract: PRP was a valid preoperative strategy to improve physical performance in patients with both NSCLC and COPD and this advantage was also maintained after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
153
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(163 citation statements)
references
References 23 publications
5
153
1
1
Order By: Relevance
“…Participants with lung cancer and comorbid chronic obstructive pulmonary disease (COPD) who received a pre-operative pulmonary rehabilitation programme (versus usual care) had significantly increased peak volume oxygen (VO 2 ) levels on the day of surgery (p < 0.0001) and 60 days post-surgery (p < 0.005). However, significant between-group differences in pulmonary function (FEV 1 ) were not observed at any time point [25]. There was a significant beneficial effect of exercise on total heart rate (p = 0.04) [22], walking distance ((p < 0.001) [22], (p = 0.001) [18], (p = 0.029) [17]), walking speed (p < 0.001) [22] and walking duration (p < 0.001) [22] compared to usual care.…”
Section: Lung Cancer Pre-surgical Exercise Versus Usual Carementioning
confidence: 82%
See 2 more Smart Citations
“…Participants with lung cancer and comorbid chronic obstructive pulmonary disease (COPD) who received a pre-operative pulmonary rehabilitation programme (versus usual care) had significantly increased peak volume oxygen (VO 2 ) levels on the day of surgery (p < 0.0001) and 60 days post-surgery (p < 0.005). However, significant between-group differences in pulmonary function (FEV 1 ) were not observed at any time point [25]. There was a significant beneficial effect of exercise on total heart rate (p = 0.04) [22], walking distance ((p < 0.001) [22], (p = 0.001) [18], (p = 0.029) [17]), walking speed (p < 0.001) [22] and walking duration (p < 0.001) [22] compared to usual care.…”
Section: Lung Cancer Pre-surgical Exercise Versus Usual Carementioning
confidence: 82%
“…Standard care varied according to individual institutions whereby verbal or written instructions were given [15,[19][20][21], physical activity was delivered in the rehabilitation setting post-treatment [22,23], generic risk management and active mobilisation was given [18] or fast-track surgery was implemented [24]. Five studies delivered interventions in the pre-treatment period only [12,17,18,[25][26][27]; the remaining studies continued the interventions during or after treatment. In total, 22 interventions were compared to a usual care control group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We are not aware of any other study associating prehabilitation and severity of complications, according to the Clavien-Dindo classification. Moreover, the vast majority of prehabilitation studies performed to date included populations with COPD preparing for pulmonary resection surgery (24)(25)(26)(27), a context which is not relevant to all patients at operative risk (12). Only two studies included populations of all thoracic surgery patients without an underlying chronic disease criterion and authors concluded an increase in VO 2 max (28) and the distance traveled to 6 minutes walking test (29).…”
Section: Discussionmentioning
confidence: 99%
“…In this perspective, randomized controlled trials suggests benefits from preoperative high intensity training in subjects with non-small-cell lung cancer bring new therapeutic modalities when addressing surgical risk for lung cancer patients. 34,35 However, exercise training in patients with NAC may represent a significant challenge.…”
Section: Implications For Clinical Decision and Researchmentioning
confidence: 99%